Strategi Desain Arsitektur Tropis untuk Mengurangi Panas dalam Hunian: Suatu Tinjauan Literatur - Wiranata, Tri Amartha; Jamaluddin, Husnirrahman; Edar, Ahmad Nadhil (Universitas Muslim Indonesia, 2025)
Humid tropical climates are characterized by high air temperatures, high humidity, and intense solar radiation, increasing the risk of thermal discomfort in dwellings. Various studies have shown that passive design strategies in tropical architecture can reduce heat in buildings and reduce reliance on mechanical cooling systems. This article presents a literature review of tropical architectural design strategies to reduce heat in dwellings, focusing on building orientation, mass configuration, natural opening and ventilation systems, shading elements, roof design, surface materials and colors, and vegetation integration. The literature reviewed comes from international and regional journals for the period ±2015–2025 related to passive design, thermal comfort, and residential buildings in hot-humid climates. The results of the study indicate that a combination of passive strategies can reduce room temperatures by 2–3 °C and save cooling energy by approximately 20–30% in tropical dwellings, especially when design is carried out from the early stages of building planning.